Evaluación de un modelo de inyección de agua para el mantenimiento de la producción en la Formación Villeta del Campo Orito (2018)
The main objective of this investigation work was to evaluate a water injection model for the maintenance of the production at Villeta Formation of Orito Field, for which a detailed description was made with the petrophysical properties and the properties of the fluids presented in the reservoir, with this information was generate a static academic model based on the degree work "Evaluación integral de yacimiento para la formación Villeta del Campo Orito" published by Carlos Andrés Cortés Daza and Nestor Oswaldo Leyva Meneses in 2005, from the maps corresponding to the static properties and all types of graphics related to the production and behavior of the fluids present in the reservoir. Later, a conceptual simulation model was processed to determine the production behavior, under the case of field prediction none injection was implemented, and additionally two injection schemes that were evaluated with production rates of 500 BPD and 1000 BPD in each of the wells.